An uncommon (5, 5)-connected 3D metal organic material for selective and sensitive sensing of nitroaromatics and ferric ion: experimental studies and theoretical analysis. Issue 25 (15th June 2017) - Wang, Jun; Wu, Xi-Ren; Liu, Jian-Qiang; Li, Bao-Hong; Singh, Amita; Kumar, Abhinav; Batten, Stuart R.
Abstract : A new 5-connected (4 4 )(6 6 ) anionic framework can act as a fluorescent sensor for nitroaromatics and Fe 3+ . The possible emission quenching mechanism in presence of nitroaromatics have been addressed by theoretical calculations. Abstract : An unexploited pentacarboxylate ligand, 2, 5-bis(3′, 5′-dicarboxylphenyl)-benzoic acid (H5 L), was designed and used for the preparation of metal organic material using Zn 2+ as a node. The new compound, {(Me2 NH2 )[Zn2 (L)(H2 O)]·0.5DMF} n (1 ) (DMF = dimethylformamide), has been synthesized and structurally characterized. The topology of the 5-connected anionic framework may be described as (4 4 )(6 6 ) (Schläfli symbol) based on {M2 (CO2 )5 } molecular building blocks (MBBs) and L ligands in1 . It has been demonstrated that1 can act as a fluorescent sensor for highly sensitive detection of nitroaromatics and Fe 3+, with a detection limit of 0.54 ppm for 2, 4, 6-trinitrophenol (TNP) and 0.81 ppm for Fe 3+ . The possible emission quenching mechanism in the presence of nitroaromatics has been addressed by theoretical calculations.